OCORRÊNCIA DO FUNGO Hirsutella SP. EM ADULTO DA BROCA DOS EUCALIPTUS Phoracantha semipunctata (FABRICIUS) (COLEOPTERA, CERAMBYCIDAE) - Berti Filho, Evoneo; Alves, Sérgio Batista; Cerignoni, João Angelo (REVISTA DE AGRICULTURA, 2015)
OCORRÊNCIA DO FUNGO Hirsutella SP. EM ADULTO DA BROCA DOS EUCALIPTUS Phoracantha semipunctata (FABRICIUS) (COLEOPTERA, CERAMBYCIDAE)